Bridging the gap: an investigation of biosurfactants-polymer systems - Abhyankar, Isha; Hirlekar, Swarali; Prabhune, Asmita; Nisal, Anuya (Current Opinion in Colloid & Interface Science, 2024)
Biosurfactants (BSs) have been extensively researched due to their potential applications in various fields, including textiles, cosmetics, pharmaceuticals, agriculture, and oil remediation. These BSs possess a diverse range of physical, chemical, and biological properties. In recent years, researchers have combined these biosurfactants with both natural and synthetic polymers, resulting in the development of advanced material systems that exhibit a unique combination of properties. This review focuses on highlighting the recent advancements in these biosurfactant-polymer material systems and identifies existing gaps in the literature. The combination of biosurfactants with polymers has led to the formation of interpenetrated hydrogels, films, chemically modified surfaces, vesicles, functionalized nanofiber nonwoven mats, nano-formulations, and nano-assemblies. Some studies have also investigated the interactions between biosurfactants and polymer molecules. In most cases, non-specific, non-covalent interactions, such as electrostatic interactions, hydrogen bonding, and hydrophobic interactions have been found to govern the properties of these systems. Moreover, promising results have been achieved through the covalent modification of polymer surfaces, followed by functionalization using biosurfactant molecules. The literature demonstrates that these advanced materials could find applications in various fields, including drug delivery, bioremediation, biomedical materials, and as antimicrobial agents. These findings indicate the promising potential of biosurfactant-polymer systems for future advancements in these areas.